A Study in Redistribution and Consumption - Bronfenbrenner, M.; Yamane, Taro; Lee, C. H. (The Review of Economics and Statistics, 1955)
AT least since Mandeville's Fable of the Bees (I728), there have been underconsumptionists who have ascribed trade depressions to deficiency in consumption expenditures.' Underconsumptionist thought may further be subdivided into two schools. Monetary underconsumptionism, which does not concern us here, blames underconsumption upon flaws in the processes of creation and circulation of money and credit. Social Credit movement in Great Britain and the Greenback movement in the United States may serve as illustrations. Since Marx and Rodbertus, however, the deficiency of consumption expenditures (and purchasing power) has been ascribed more commonly to maldistribution of real income. This we shall call maldistributionist or real underconsumption. During prosperity, income is concentrated in the higher brackets, where a large fraction is saved. If the savings are hoarded, there arises an immediate deficiency in consumption. If the savings are invested, the deficiency is only postponed until the day when additional consumption goods are produced because of the new investment, and come on to market without additional purchasing power to absorb them. Such, in briefest outline, is the position of the late John A. Hobson, the leading English-language representative of real underconsumptionism in the twentieth century.2 In this view, the principal means to prevent and to remedy depressions is substantial redistribution of income in the direction of greater eaualitv. In addition to Rodbertus, Marx, Hobson, and other leaders of the economic underworld, Keynes has given this position an indirect accolade in the General Theory,3 and it has been adopted by a substantial fraction of the neo-Keynesian school. Virtually all of the discussion, however, has been carried on in a quantitative semi-vacuum, which is to say, without any precise ideas as to the quantitative importance of possible income redistributions. It was of course recognized from the outset that personal savings rise faster than personal income, or in current jargon, that individuals' average propensities to save rise with their incomes. What was not recognized, however, was that for redistribution problems the relative marginal propensities to save of different income classes were likewise important, since redistribution involves shifts between income classes at the margin. To cite an extreme case, if all individuals' marginal propensities to save were identical, equalization of incomes would have no effect whatever on aggregate consumption and saving, however great might be the disparities in average propensities between rich and poor.4 Keynes himself, it would appear, was guilty of some inconsistency on this subject. He considered his consumption function relatively stable (which presumably means stable with respect to changes in income distribution), and at the same time he advocated income equalization in the interest of increased aggregate consumption. One of the first studies to apply modern aggregative analysis in estimating the quantitative effect of income redistribution on aggregate consumption was carried out by Harold Lubell at the Board of Governors of the Federal Reserve System.5 His study, which has been un* This study was financed by a grant from the Social Science Research Committee of the University of Wisconsin. 1 Harry G. Johnson cites the French Physiocrat Boisguillebert a century earlier as maintaining that trade would be more active if taxation fell on the rich than if it fell on the poor, which comes closer than Mandeville to a maldistributionist position. The Macro-Economics of Income Redistribution, in Alan T. Peacock (ed.), Income Redistribution and Social Policy (London, I954), p. I9. 2 For a full presentation of Hobson's views, see Erwin E. Nemmers, Hobson and Underconsumption (unpublished Ph.D. dissertation, Wisconsin, I953). We have called Hobson a twentieth-century writer, :but the initial presentations of his views appeared before the turn of the century. 'Keynes, General Theory, pp. 369-74. ' average propensities are important in this case only if ioo per cent of one individual's income is being taken away, or in a case where income is being given to individuals who had none before. 5 Harold Lubell, Effects of Income Redistribution on Consumers' Expenditures, American Economic Review, xxxvii (March 1947), 157-70, corrected in part, ibid., xxxvii (December 1947), 930. Lubell results appear to have furnished statistical